MORFOLOGI BAHASA DAYAK POMPAKNG - Mustaqim, Nursuki; Hanye, Paternus; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe Pompakng Dayak language consists of morphemes and the word Morfem is the smallest element that has a meaning that can be a word or part of a word. Morphem BDP also has a form, namely the bound form and the free form. Morphological processes that occur in Dayak Pompakng language include, affix, reduplication, and compounding. Affix form in Dayak Pompakng language there are three kinds, namely prefix, suffix and confix. Prefix in Dayak Pompakng language there are six kinds, namely (bo-), (meN-), (le-), (ko-), (poN-), (to-). There are two kinds of suffixes, namely (-lah), and (-nih). Meanwhile, there are three types of confixes, namely (ko-an), (le-nih), (meN-nih). Dayak Pompakng language there are only two repetitions, the whole repetition and partial recurrence. The composition in the BDP has the characteristics, (1) One or all of its elements are the subject of the word, and (2) when viewed from the nature of its construction the elements of the compound word canâ€™t be separated or impossible to change its structure. While the type of the word mejemuk consists of 2 that is, based on the relationship of elements that support it and based on the construction of the class he said.Â Keywords: morphology, language, pompakng